CONTROL OF STOCK CHANGES IN TIME - Ya. S. Antoniuk; T. R. Kisel (Наука и техника)
The paper proposes methodology for control of stock changes in time. This methodology allows to optimize changes of stocks and accompanying changes of monetary stock in time. In order to control changes of stock in time indices of bankruptcy probability and also profit together with limitations offered by the author which unites profit maximization and provision of enterprise solvency as a unit are taken as optimum criteria.